Tanggung Jawab Pihak Ketiga (MAXIM) Dalam Pemberian Ganti Rugi Kepada Konsumen Korban Kekerasan Seksual Oleh Pengemudi di Kabupaten Bone Bolango (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Sexual violence is a serious problem that affects many individuals throughout the world. In this context, drivers associated with acts of sexual violence are often the focus of attention. The responsibility of third parties, such as transportation service providers or application platforms, can be an important factor in providing compensation to victims who have experienced sexual violence by drivers. This research aims to analyze the responsibilities of third parties, especially companies providing transportation services or application platforms that facilitate meetings between drivers and passengers, in providing compensation to victims of sexual violence. This research uses an analytical approach by collecting data and information related to the policies and practices implemented by the Maxim company. The results of the analysis show that the responsibility of third parties, in this case Maxim, has an important role in providing compensation to victims of sexual violence. Maxim is expected to have a clear and transparent policy in handling reports of sexual violence involving their drivers. They should also provide safe and reliable communication channels for victims to report incidents. Apart from that, Maxim must also ensure that there is a fair and thorough investigation process for reports of sexual violence. They must cooperate with law enforcement authorities to ensure that legal action is taken against drivers involved in sexual violence. In addition, Maxim must provide support and assistance to victims of sexual violence, including access to counseling and mentoring services. This research concludes that the responsibility of third parties, such as Maxim, is very important in providing compensation to victims of sexual violence by drivers. Such companies must have clear policies, effective procedures, and open channels of communication so that victims feel heard and protected. In an effort to prevent sexual violence, such companies must also continue to increase awareness and training for their drivers regarding policies and prohibited actions in the context of sexual violence.